The Association of Glucocorticosteroid Treatment with WBC Count in Patients with COPD Exacerbation - Amit Frenkel (Journal of Clinical Medicine, 2019)
Systematic glucocorticosteroids (GCS) are used to treat chronic obstructive pulmonary disease (COPD) and can cause leukocytosis. Distinguishing the effect of GCS on leukocyte level from infection-induced leukocytosis is important. We sought to quantify the effect of chronic GCS treatment on leukocytosis level in patients with COPD exacerbation. We reviewed the records of patients with COPD exacerbation and fever hospitalized in a tertiary medical center in 2003−2014. Patients were classified according to the GCS treatment they received: chronic GCS treatment (CST), acute GCS treatment (AST), and no prior GCS treatment (NGCS). We used the eosinophil absolute count as a marker of compliance and efficacy of steroid treatment. The primary outcome was the maximal white blood cell (WBC) count within the first 24 h of admission. Of 834 patients, 161 were categorized as CST, 116 AST, and 557 NGCS. The overall maximal leukocyte count was higher and the eosinophil count lower in the two GCS therapy groups. In patients with COPD exacerbation and fever, acutely treated with GCS, the mean increase in the WBC count was more evident when the eosinophils were undetectable (absolute count of zero). This supports leukocytosis level as a marker of disease course in COPD and fever.